Current Diagnostic and Treatment Approach of Clostridioides difficile Infection - Bella Yunita; Achmad Fauzi (Acta Medica Indonesiana, 2023)
C. difficile infection is related to wide spectrum of disease, from self-limiting diarrhea to fulminant disease that can cause toxic megacolon or pseudo-membrane colitis. Difficult approach to diagnose this disease is also problem. C. difficile infection is diagnosed when diarrhea occurred in high risk patient with positive result of GDH or NAAT test that was confirmed by positive result of toxin test. Nevertheless, there is limited choice of treatment in Indonesia. Thus, the main priority of C. difficile infection  in Indonesia is associated with its prevention, by implementing standard precaution and use of rational antimicrobial.